Taxonomic review of the genus Kelissa Ravenna (Iridaceae) - Deble, Leonardo Paz (Balduinia, 2022)
Taxonomic review of the genus Kelissa Ravenna (Iridaceae) A taxonomic review of the genus Kelissa is carried out. This genus is constituted by a single species, Kelissa brasiliensis, endemic to the state of Rio Grande do Sul, Brazil. Kelissa brasiliensis prospers in mountainous regions associated with grasslands, mainly in the southeastern part of the state of Rio Grande do Sul, but with populations extending to the central and western regions of the state. Kelissa brasiliensis is described and illustrated in detail and its geographic distribution is represented on a map. Data on etymology, geographic distribution, habitat, phenology, conservation, uses and vernacular names are provided, as well as discussions of taxonomic relationships of Kelissa with related taxa. A dichotomous key for distinguishing the genera of Iridaceae-Tigridieae from South America is presented. Key Words: Pampa Biome, Grasslands, Cypelloid, Tigridieae.